ANALISIS PERENCANAAN KEBUTUHAN SUMBER DAYA MANUSIA DALAM KESEHATAN DENGAN METODE WORKLOAD INDICATORS OF STAFFING NEED (WISN) DI PUSKESMAS NAMORAMBE - Sri Sudewi Pratiwi Sitio; Usrawati Pasaribu; Dewi Safitri Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Public Health Center is a technical unit of health official in regency / town that responsible to take care health development in work area. The success of health care in organization viewed from the availability of health workers. Human resources is a major asset of health center, it is necessary to do planning and calculation of health workers who are in any specific units. The purpose of this research was to see the representation of necessity planning of human resources in health by using the method of Workload Indicators Of Staffing Need (WISN) at health center of Namorambe. The type of this research was quantitative descriptive research by using observation, interviews, questionnaires and document study. The sample of this research were all health workers at health centers of Namorambe on work units, namely: General checkup 9 persons, Emergency Room 8 persons, Dental chekup 4 persons, Maternal and child health centers 3 person, Pharmacies 5 persons, Poli of children 2 persons, obstetrician at KB 1 person, and analysis at Laboratory 1 person. Based on the calculations by the method of WISN Human Resources needs, to persons health workers in general checkup, Emergency Room needs one person, and it needs one person for Pharmacies. It is expected for human resources development, especially in the Section of Planning and Human Resources Development of North Sumatra Health Official so that follow up the proposal on the demand for health workers. Keywords: Public Health Center, Human Resource Necessity, Method of WISN